Renal progenitors derived from human iPSCs engraft and restore function in a mouse model of acute kidney injury - Imberti, Barbara (Sci Rep, 2015)
Acute kidney injury (AKI) is one of the most relevant health issues, leading to millions of deaths. The magnitude of the phenomenon remarks the urgent need for innovative and effective therapeutic approaches. Cell-based therapy with renal progenitor cells (RPCs) has been proposed as a possible strategy. Studies have shown the feasibility of directing embryonic stem cells or induced Pluripotent Stem Cells (iPSCs) towards nephrogenic intermediate mesoderm and metanephric mesenchyme (MM). However, the functional activity of iPSC-derived RPCs has not been tested in animal models of kidney disease. Here, through an efficient inductive protocol, we directed human iPSCs towards RPCs that robustly engrafted into damaged tubuli and restored renal function and structure in cisplatin-mice with AKI. These results demonstrate that iPSCs are a valuable source of engraftable cells with regenerative activity for kidney disease and create the basis for future applications in stem cell-based therapy.